Associations Between Adolescent Problematic Internet Use and Relationship Problems in Chinese Families: Findings from a Large-scale Survey - Alimila Hayixibayi; Esben Strodl; Wei-Qing Chen; Adrian B Kelly (JMIR Publications, 2022)
BackgroundProblematic internet use (PIU) is prevalent among Chinese adolescents. There is a need to better understand how the quality of parent-adolescent relationship is associated with adolescent PIU to guide the development of effective prevention and early intervention programs. ObjectiveThis study aims to evaluate parent-adolescent conflict and parenting styles as potential risk factors associated with adolescent PIU. MethodsA sample of 6552 students (aged 10-19 years) from 22 schools in Guangdong, China, was recruited. The participants completed self-report questionnaires measuring their perceptions of conflict with their parents (involving verbal conflict, emotional abuse, and physical abuse) as well as their perceptions of their parents' parenting styles (including parental care and parental control as measured by the Parental Bonding Inventory), and PIU using the Adolescent Pathological Internet Use Scale. Grade level and gender were examined as moderators of these associations. ResultsUsing multiple regression analyses, we found that greater mother-adolescent conflict, father-adolescent conflict, and parental control, and lower levels of parental care, were associated with higher levels of adolescent PIU (P<.001). The association between mother-adolescent conflict and PIU was stronger in older students than in younger students (P=.04), whereas the association between father-adolescent conflict and PIU was stronger in male students than in female students (P=.02). Compared with those who reported no mother-adolescent conflict, participants who experienced verbal conflict and emotional abuse, but not physical abuse from their mothers, reported higher levels of PIU (P<.001). Compared with those who reported no father-adolescent conflict, participants who experienced verbal conflict, emotional abuse, and physical abuse from their fathers had significantly higher levels of PIU (P<.001, P<.001, and P=.02, respectively). ConclusionsThese findings point to the value of interventions to reduce parental verbal conflict, emotional abuse, and physical abuse, and to increase positive parenting styles, to lower the risk of PIU in Chinese adolescents.